Corporate governance - Kim, Kenneth A.; Nofsinger, John R. (Pearson/Prentice Hall, 2010)
A perfect supplement for courses in Corporate Finance, Accounting, a variety of Management courses like Strategy, Ethics and/or Business and Society, and Business Law. An overview of the corporate governance system in a flexible, modular format. Today the term "corporate governance" is familiar to almost everyone, mostly because of the emergence of so many shocking corporate scandals. Corporate Governance, in its flexible, modular format, sheds light on these recent problems and scandals through a detailed explanation of the corporate governance mechanism, and the various incentives within today's governance system, while offering potential solutions in context. The Third Edition of Corporate Governance includes up-to-date material on the economic crisis of 2008-2009 and offers current scholarly research in Recent Research boxes throughout the text